Different visual stimuli affect body reorientation strategies during sidestepping - Lee, M. J. C.; Lloyd, D. G.; Lay, B. S.; Bourke, P. D.; Alderson, J. A. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Sidestepping in response to unplanned stimuli is a high-risk maneuver for anterior cruciate ligament (ACL) injuries. Yet, differences in body reorientation strategies between high- and low-level soccer players prior to sidestepping in response to quasi-game-realistic vs non-game-realistic stimuli, remain unknown. Fifteen high-level (semi-professional) and 15 low-level (amateur) soccer players responded to a quasi-game-realistic one-defender scenario (1DS) and two-defender scenario (2DS), and non-game-realistic arrow-planned condition (AP) and arrow-unplanned condition (AUNP). The AP, 1DS, 2DS to AUNP represented increasing time constraints to sidestep. Selected biomechanics from the penultimate step to foot-off were assessed using a mixed-model (stimuli × skill) ANOVA (P < 0.05). Step length decreased in the defender scenarios compared with the arrow conditions. Support foot placement increased laterally, away from mid-pelvis, with increasing temporal constraints. Greater trunk lateral flexion in the 1DS, 2DS, and AUNP has been associated with ACL injury onsets. Higher level players pushed off closer to their pelvic midline at initial foot contact in the 2DS especially. Higher level perception of game-realistic visual information could have contributed to this safer neuromuscular strategy that, when understood better, could potentially be trained in lower level players to reduce ACL injury risk associated with dangerous sidestepping postures.